"MODERN PROBLEMS OF INCREASING INTELLECTUAL POTENTIAL IN TEACHING RUSSIAN TO UNIVERSITY STUDENTS" - Maseeva Muzaffara Kutfiddinovna (Journals Park Publishing, 2022)
In the modern multipolar world, when globalization processes are intensifying in all spheres of social and humanitarian reality, there are natural changes and needs for the formation, formation and development of a personality with polyphonic thinking. Scientists note that the modern developing world cannot be mastered by people with a monotonous type of thinking, that an increasing number of problems due to their polymodal nature requires interdisciplinary analysis and synthesis. When solving them, it is necessary to search for consensus between various alternative positions and ways of thinking.
Keywords: Education; students; development